Retrospective Observational Analysis in a Cohort Patients in Treatment with Alirocumab and Evolocumab: Focus on C-LDL Values - Coppolino, Salvatore (Universitas Padjadjaran, Indonesia, 2025)
Hypercholesterolemia is the main risk factor for cardiovascular disease. Statins are the drugs of first choice, but many patients fail to reach the recommended levels of LDL cholesterol, or are intolerant. The PCSK9 inhibitor drugs (Alirocumab and Evolocumab) are anti-PCSK9 antibodies: represent a new pharmacological approach, and have been approved as an adjunct to Statins or in intolerant patients. The aim of the work was to carry out a retrospective analysis of a cohort of patients treated with anti-PCSK9 antibodies. The AIFA Therapeutic Plans were received by the Pharmacy from 01/01/2021 to 06/30/2023 by extrapolating data such as: sex, age, prescribed PCSK-9, adverse reactions, LDL cholesterol values before treatment and at the first re-evaluation. Out of 329 patients on treatment, 215 (65.3%) were treated with Evolocumab, 114 (34.7%) with Alirocumab. The 329 patients analyzed , have an average age of 64 years (minimum 30 - maximum 87). Our analysis has highlighted that in post-treatment patients the percentage change in LDL cholesterol values compared to baseline is equal to 59.8% in line with what was observed in the ODISSEY and FOURIER studies. PCSK9 inhibitors are state-of-the-art therapies and are well tolerated and effective in the management of the statin-intolerant patient, or as an adjunct to existing lipid-lowering therapies. Furthermore, statins increase serum PCSK9 levels; therefore, the best effect of these inhibitors is seen in combination with them